PORTAL TRACER STUDY BERBASIS SOCIAL NETWORK DALAM MENDUKUNG PENGGALIAN DATA ALUMNI DENGAN CLUSTERING ALGORITHM - Marisa, Fitri; Mumpuni, Indah Dwi (DINAMIKA DOTCOM, 2018)
This study aims to build a portal system tracer study based on multiple platforms equipped with clustering algorithm to support data processing alumni institutions. The method used to build the portal is the social network, while the technique used to extract the data is clustering algorithm. The result of the research is a portal website tracer study based on social network, and continued with clustering of alumni data based on study time and waiting time.Keywords: tracer study, social network, clustering algorithm, institution